2017
DOI: 10.2169/internalmedicine.56.8168
|View full text |Cite
|
Sign up to set email alerts
|

Successful Switch to Golimumab for Eosinophilia and Skin Symptoms Related to Multiple Biologics in a Patient with Rheumatoid Arthritis

Abstract: Biologics used in the treatment of rheumatoid arthritis (RA) rarely cause eosinophilia. We herein report a patient with RA being treated with infliximab, adalimumab, and tocilizumab who developed eosinophilia with skin symptoms. Interestingly, the marked eosinophilia and skin symptoms did not reappear after the patient's medication was switched to golimumab. In this case, the presence of biologics-specific antibodies suggested that immunogenicity caused the eosinophilia. Therefore, switching to a biologic with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Thus, physiologically higher levels of eosinophils in blood seem to have a positive role in the treatment of RA. On the other hand, BT-induced eosinophilia, described also in our observation, was related with skin symptoms and hypersensitivity (Azuma et al, 2017[ 3 ]).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, physiologically higher levels of eosinophils in blood seem to have a positive role in the treatment of RA. On the other hand, BT-induced eosinophilia, described also in our observation, was related with skin symptoms and hypersensitivity (Azuma et al, 2017[ 3 ]).…”
Section: Discussionsupporting
confidence: 81%
“…Several studies linked the presence of hematological disorders with RA disease activity, treatment prognosis, the onset of additional hematological abnormalities, or with conventional synthetic disease-modifying anti-rheumatic drugs (DMARDs) co-treatment (Autrel-Moignet and Lamy, 2014[ 2 ]; Azuma et al, 2017[ 3 ]; Bessissow et al, 2012[ 6 ]; Boilard et al, 2012[ 7 ]; Hensel et al, 2017[ 20 ]). The results presented here have shown that BT may contribute to disruption of hematological homeostasis, which could be followed by the onset of side effects and lead to therapy switch.…”
Section: Discussionmentioning
confidence: 99%
“…The patient took oral prednisolone (1 mg/kg/day) (8). However, this treatment did not result in his dramatic response; hence, we added hydroxyurea (3 g/day) (9, 10) accompanied by MTX (17.5 mg single weekly dosage), folic Acid (1 mg/day), and golimumab (50 mg SC qMonth) (11). Two months later, his motion problem symptoms improved, and it led to a gradual reduction of redness in his skin.…”
mentioning
confidence: 99%